Femtosecond Mode-locked Fiber Laser at 1 μm Via Optical Microfiber Dispersion Management - Lizhen Wang (Nature Portfolio, 2018)
Abstract Mode-locked Yb-doped fiber lasers around 1 μm are attractive for high power applications and low noise pulse train generation. Mode-locked fiber lasers working in soliton and stretched-pulse regime outperform others in terms of the laser noise characteristics, mechanical stability and easy maintenance. However, conventional optical fibers always show a normal group velocity dispersion around 1 μm, leading to the inconvenience for necessary dispersion management. Here we show that optical microfibers having a large anomalous dispersion around 1 μm can be integrated into mode-locked Yb-doped fiber lasers with ultralow insertion loss down to −0.06 dB, enabling convenient dispersion management of the laser cavity. Besides, optical microfibers could also be adopted to spectrally broaden and to dechirp the ultrashort pulses outside the laser cavity, giving rise to a pulse duration of about 110 fs. We believe that this demonstration may facilitate all-fiber format high-performance ultrashort pulse generation at 1 μm and may find applications in precision measurements, large-scale facility synchronization and evanescent-field-based optical sensing.